Impact of a single-set blood culture restriction during the 2024 national blood culture bottle shortage on patient outcomes: an interrupted time series analysis - Joseph B. Ladines-Lim; Bailey Van; Leigh Cressman; Warren B. Bilker; Laurel Glaser; Kathleen Degnan; Michael Z. David (Infection Control & Hospital Epidemiology, 2026)
Abstract Objective: To evaluate the clinical and stewardship consequences of a single-set blood culture restriction implemented during the 2024 national blood culture bottle shortage. Design: Interrupted time series analysis of hospitalizations from June 26, 2023, to June 25, 2025. Setting: Two tertiary hospitals in an urban academic health system. Patients: 116,341 inpatient hospitalizations, including 31,034 with ≥1 blood culture obtained. Intervention: A systemwide electronic health record order restriction from June 26 to December 23, 2024, limiting clinicians to one blood culture set per patient every 24 hours. Results: In-hospital mortality or hospice discharge declined before restriction (−1.3%/week; P < .001), flattened during restriction (+0.8%/week; P = .20), and declined again after restriction (−2.8%/week; P < .001). Overall blood culture positivity increased from 9.6% prerestriction to 11.2% during restriction and decreased to 10.2% postrestriction. Upon restriction onset, hospitalizations with ≥1 blood culture decreased 29.7% ( P < .001). Among hospitalizations with ≥1 blood culture, mean cultures per hospitalization decreased 52.6% ( P < .001), time to first culture increased 39.5% ( P < .001), and time to first antimicrobial increased 13.8% ( P = .04). Days of antimicrobial therapy increased among hospitalizations with and without blood cultures by 12.6% ( P = .001) and 10.6% ( P < .001), respectively. Conclusions: A near-universal single-set blood culture restriction was associated with decreased and delayed diagnostic testing, delayed antimicrobial initiation, increased antimicrobial exposure, and temporal changes in clinical outcomes. Crisis-driven diagnostic stewardship interventions should include indication-specific guidance and real-time safety monitoring.